(untitled) (Global Journal of Management and Business Research, 2013)
The international trade policy in the end of the first decade of the XXI century have been strongly affected by the force of the economic crisis. The changes are evident in the growing importance of international trade to national economies and to domestic groups within those economies, in the closer linkages between trade and other international issues. Realistic point is important trends in the global trade regime during the economic crisis.